Genetic heterogeneity and mitochondrial DNA heteroplasmy in Leber's hereditary optic neuropathy. Issue 12 (December 1989) - Holt, I J; Miller, D H; Harding, A E
Abstract : Analysis of mitochondrial DNA from patients with Leber's hereditary optic neuropathy and their relatives showed that the previously reported mutation at base pair (bp) 11778, shown by loss of a recognition site for the restriction endonuclease SfaNI, was present in only four out of eight families. This mutation was associated with a poor prognosis for visual recovery, whereas four of five affected males without the 11778 bp mutation followed for four years or more had regained useful vision. All but one of the subjects showing the SfaNI site loss had a variable mixture of mutant and normal mitochondrial DNA in peripheral blood, and the relative proportions appeared to be correlated with the risk of developing or transmitting Leber's hereditary optic neuropathy.